Cosmological application on five-dimensional teleparallel theory equivalent to general relativity - Nashed, Gamal G. L. (Chinese physics B, 2012)
A theory of（4＋1）-dimensional gravity has been developed on the basis of which equivalent to the theory of general relativity by teleparallel.The fundamental gravitational field variables are the 5-dimensional（5D） vector fields（pentad）,defined globally on a manifold M,and gravity is attributed to the torsion.The Lagrangian density is quadratic in the torsion tensor.We then apply the field equations to two different homogenous and isotropic geometric structures which give the same line element,i.e.,FRW in five dimensions.The cosmological parameters are calculated and some cosmological problems are discussed.